Targeting NF-kappa B Signaling by Artesunate Restores Sensitivity of Castrate-Resistant Prostate Cancer Cells to Antiandrogens - Jessica J. Nunes; Swaroop Kumar Pandey; Anjali Yadav; Sakshi Goel; Bushra Ateeq (2017)
Androgen deprivation therapy (ADT) is the most preferred treatment for men with metastatic prostate cancer (PCa). However, the disease eventually progresses and develops resistance to ADT in majority of the patients, leading to the emergence of metastatic castration-resistant prostate cancer (mCRPC). Here, we assessed artesunate (AS), an artemisinin derivative, for its anticancer properties and ability to alleviate resistance to androgen receptor (AR) antagonists. We have shown AS in combination with bicalutamide (Bic) attenuates the oncogenic properties of the castrate-resistant (PC3, 22RV1) and androgen-responsive (LNCaP) PCa cells. Mechanistically, AS and Bic combination inhibits nuclear factor (NF)-κB signaling and decreases AR and/or AR-variant 7 expression via ubiquitin-mediated proteasomal degradation. The combination induces oxidative stress and apoptosis via survivin downregulation and caspase-3 activation, resulting in poly-ADP-ribose polymerase (PARP) cleavage. Moreover, preclinical castrate-resistant PC3 xenograft studies in NOD/SCID mice (n =28, seven per group) show remarkable tumor regression and significant reduction in lungs and bone metastases upon administering AS (50 mg/kg per day in two divided doses) and Bic (50 mg/kg per day) via oral gavage. Taken together, we for the first time provide a compelling preclinical rationale that AS could disrupt AR antagonist-mediated resistance observed in mCRPC. The current study also indicates that the therapeutic combination of Food and Drug Administration-approved AS or NF-κB inhibitors and AR antagonists may enhance the clinical efficacy in the treatment of mCRPC patients.